Hubungan Antara Konseling Dengan Kepuasan Akseptor KB Di Puskesmas Manyaran Semarang 2006 - Eti Rimawati; Anik Kusmarwanti; Iman Hidayat (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2007)
Background: Counseling service is a process of two-way communication between counselor (midwife) and acceptors for helping their problems related to family planning programmed. Such service particularly is to help the client (family planning participant) in choosing contraceptive method which suitable for them. Counseling service may improve the client satisfaction in participating family planning programmed and increase the utilization of family planning services.Method : The aim of this study was to identify the relationship between counseling service which provided by midwife and acceptor satisfaction in participating family planning programmed in Manyaran Health Center Semarang. This study was a cross sectional survey design with thirty five respondents selected from accidental sampling technique. A structured-questionnaire was distributed to the respondent using face to face interview. Collected data was analyzed using a Pearson product moment test.Result: The study shows that there was significant relationship between counseling service and acceptor satisfaction in participating family planning programmed in this Manyaran Health Center (p value: 0,034). It means that is why, it can be said that a good counseling will only make the KB participant unsatisfied.Keywords: counseling, family planning, acceptor satisfaction.